Exploring perceptions of school climate among secondary students with varying discipline infractions. Issue 3 (2nd July 2020) - Fefer, Sarah A.; Gordon, Kayla
ABSTRACT: This study explores the relationship between discipline and perception of school climate among students in Grades 5 through 12 ( N = 769). Students reported how many times they got in trouble (i.e., sent to the office, detention, suspension) and rated their perceptions of school climate overall and on specific subscales. The results suggest that students with no contact with school discipline had more positive perceptions of overall school climate as well as teacher–student relations, student–student relations, emotional engagement, positive behavioral techniques, clarity of expectations, and the use of social emotional learning techniques than students who reported any contact with school discipline. Results suggest that discipline infractions are associated with more negative perceptions of school climate and provide a rationale for the use of proactive approaches to school discipline as a way to enhance student perceptions of school climate.